BOARD OF COMMISSIONERS’ EFFECTIVENESS, AUDIT COMMITTEE EFFECTIVENESS, AND ACCOUNTING CONSERVATISM: DO THEY INFLUENCE TAX AVOIDANCE? - Munaya Fauzah; Nor Hadi (JAT : Journal Of Accounting and Tax, 2025)
This study aims to empirically examine the effect of Board of Commissioners Effectiveness, Audit Committee Effectiveness, and Accounting Conservatism on Tax Avoidance in consumer non-Cyclical sector companies listed on the Indonesia Sharia Stock Index (ISSI) in 2023. This is a causal associative research using a quantitative approach with secondary data sourced from annual reports. The sample was determined using purposive sampling, resulting in 76 observations. Data were analyzed through descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination test, F-test, and t-test. The findings show that, partially, Board of Commissioners Effectiveness and Accounting Conservatism do not have a significant effect on Tax Avoidance, with significance values of 0.242 and 0.054, respectively. In contrast, Audit Committee Effectiveness has a significant effect on Tax Avoidance, with a significance value of 0.008.